2003
DOI: 10.1080/07481180302892
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of Psychosocial Distress After Suicide, Sids and Accidents

Abstract: This article compares the outcome and predictors of psychosocial distress of parents bereaved by young suicides, sudden infant death syndrome (SIDS), and child accidents. One objective is to explore whether suicide bereavement is more difficult for those left behind than other forms of bereavement. Data have been collected from 140 families, consisting of 232 parents, by the use of the Impact of Event Scale, the General Health Questionnaire, and the Inventory of Traumatic Grief. Qualitative aspects of bereavem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
202
1
7

Year Published

2008
2008
2018
2018

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 243 publications
(223 citation statements)
references
References 40 publications
13
202
1
7
Order By: Relevance
“…Dyregrov, Nordanger and Dyregrov (2003) found that one of the most significant predictors of psychosocial distress was not having surviving children. Similarly, Wijngaardsde Meij et al (2005) found that parents had lower levels of grief when they had other children.…”
Section: Sociodemographic and Situational Factorsmentioning
confidence: 99%
“…Dyregrov, Nordanger and Dyregrov (2003) found that one of the most significant predictors of psychosocial distress was not having surviving children. Similarly, Wijngaardsde Meij et al (2005) found that parents had lower levels of grief when they had other children.…”
Section: Sociodemographic and Situational Factorsmentioning
confidence: 99%
“…De plus, plusieurs études comparatives (de Groot et al, 2006 ;Dyregrov et al, 2003 ;Murphy et al, 2003 ;Harwood et al, 2002 ;Kitson, 2000 ;Bailley et al, 1999 ;Grad et Zavasnik, 1999 ;Reed, 1998 ;Cleiren et al, 1996 ;Séguin et al, 1995aSéguin et al, , 1995bCleiren et al, 1994 ;Farberow et al, 1992 ;Silverman et al, 1994Silverman et al, -1995Barrett et al, 1990 ;McNiel et al, 1988) observent les mêmes résultats et constatent qu'il y a plus de ressemblances que de différences entre les groupes d'endeuillés (morts par suicide, par accident, morts naturelles soudaines ou anticipées) au niveau de la symptomatologie et de ses manifestations (dépression, anxiété, détresse subjective, signes de deuil compliqué et ajustement à la perte), particulièrement lorsqu'il s'agit de décès traumatiques (accident, homicide, etc. ).…”
Section: Introductionunclassified
“…Physical and mental impairments and disturbances related to bereavement include heart problems, cancer, and symptoms of depressive and anxiety disorders (Beautrais, 1999;Clayton, 1990;Hall & Irwin, 2001;Sanders, 1999;Zisook & Shuchter, 1993), and post-traumatic stress (Beautrais, 1999;Dyregrov, Nordanger & Dyregrov, 2003). The nature and intensity of these impairments and disturbances will, naturally, be dependent upon the given circumstances in each particular case.…”
Section: Impact Of Bereavement On Individualsmentioning
confidence: 99%